Experimental analysis of hybrid metal matrix composite reinforced with Al2O3 and graphite. Issue 1 (31st December 2022) - Paul, R. Christu; Joseph, Raja; Nadana Kumar, V.; Booma Devi, P.; Manigandan, S.
Abstract : Recently the development and use of metal matrix composites. instead of conventional metals, has led to manufacturing cost optimisation to meet various light weight to strength. The MMC has several applications in the field of automotive and aerospace sectors. The paper presents the results of tribological research on Al–Si, Al2 O3 and graphite-aluminium metal matrix composite material. It analyses the mechanical properties and compares among themselves with different weight fraction samples. This composite is used as high-tech construction material in many applications, particularly for power to weight applications like pistons, cylinder liners, and bearings. The tribological properties of these materials can be significantly changed by the introduction of graphite, silicon carbide particles. The wear tests were carried out using the pin-on-disc tribometer and analysed by Ducom software. The sliding and wear resistance of the matrix and composite alloy specimens have been subjected to comparative analysis. It was demonstrated that the composite reinforced with graphite is characterised by a lower friction coefficient and lower wear rate was achieved by adding silicon carbide to the matrix composite.